Application of diffusion tensor imaging technology in glaucoma diagnosis - Wang, Jiaqi; Zhang, Yaqiong; Meng, Xueyu; Liu, Gang (Frontiers in Neuroscience, 2023)
Glaucoma is the first major category of irreversible blinding eye illnesses in the world, and its main cause is the death of retinal ganglion cells and their axons, which results in the loss of vision. Current research indicates that glaucoma affects not only the optic nerve but also the entire visual pathway, and that glaucoma-related degenerative lesions can even be identified outside of the visual pathway. Diffusion tensor imaging (DTI) is a sophisticated magnetic resonance imaging (MRI) technique that can investigate the complete visual system, including alterations in the optic nerve, optic chiasm, optic tract, lateral geniculate body, and optic radiation. The purpose of this paper is to introduce the common diagnostic methods of glaucoma through a review of the literature, to introduce the application of DTI technology in animal models and human of glaucoma, and to describe the relationship between DTI parameter and the severity of glaucoma, which provides a more robust foundation for the degenerative characteristics of glaucoma. With the advancement of DTI technology and its coupling with artificial intelligence, deep learning, and bioengineering, DTI represents a potential future for MRI technology in glaucoma research.